Physical Asset Management Practices And Quality Service Delivery In Local Governments In Mid North Sub-Region Of Uganda - Adoko Obicci, Peter (International Journal of Social Sciences and Economic Review, 2019)
Amidst soaring use of excellent physical assets, there is less clear understanding of their weight on service delivery. Drawing on the contention that quality services delivery relies on excellent physical assets, the study aimed to establish how physical asset management practices affect quality service delivery in local governments in mid north sub-region of Uganda. Methodology: The study used cross-sectional design with a quantitative approach. A sample of 131 respondents were targeted and obtained using simple random and purposive sampling of physical asset managers in local governments. Collected data using self-administered questionnaire was analyzed quantitatively (descriptive and inferential statistics) using Statistical Program for Social Scientists (SPSS Ver. 23). Main Findings: Findings revealed that there was a positive correlation between physical asset management practices (rho.506) and quality service delivery. Accordingly, it was concluded that physical asset management practices, measured in terms of lifecycle planning, risk management, information management and performance management significantly affected quality service delivery in local governments in mid north sub-region of Uganda. Research limitations/implications: The study used quantitative approach in two local governments with probable missed out on qualitative aspects aside difficulty in generalizability. However, it enlightens theoreticians and practitioners in ensuring proper execution of physical asset management practices in engineering, infrastructure, estate, finance and above all public procurement; for the provision of quality services desired and expected by the different stakeholders. Novelty/Originality of this study: This study parallels those in developed countries which reveal that success in quality service delivery is a result of using excellent physical assets. However, in developing countries studies are nearly nonexistent. Essentially, there is a paucity of research addressing the subject creating a need to study and systematically document elevation of delivery of quality services using excellent physical assets.
Keywords: Physical Asset; Management Practices; Quality Service Delivery; Sub-region